A qualitative study exploring the perceptions of South African esports consumers towards non-endemic brands advertising through esports - Asoulin, Yael (The IIE, 2020)
Esports is a massive global phenomenon with an inexorable interest in the market itself, from both a consumer, and a brand perspective. An industry that was once dominated by endemic brands is now open for all brands to use as a means of brand extension. However, the evolution of esports demonstrates how endemic brands are more apt to being accepted by gamers on account of their specific product offerings and habitual presence in the esports scene. Non-endemic brands in particular need more than basic esports knowledge to enter the complex esports industry. The objective of this study is to explore the influence of esports advertising on the brand equity of non-endemic brands, by considering brand awareness and brand associations as mediators. This study is qualitative in nature, hence the interpretivist approach that was adopted for analysis purposes. A total of 4 in-depth voice call interviews were conducted over Zoom. Interpretation of the findings suggested that esports consumers do not foster any negative perceptions towards the involvement of non-endemic brands in the industry. Additionally, findings showed that social media advertising and player sponsorship are the best ways for non-endemic brands to enhance their brand extension through the burgeoning esports industry.
Keywords: Non-endemic brand; e-sport; E-sports industry; e-sports consumer; Brand equity; Endemic-brand